2016
DOI: 10.1007/s10557-016-6694-x
|View full text |Cite
|
Sign up to set email alerts
|

Can Adiponectin Help us to Target Diastolic Dysfunction?

Abstract: Adiponectin is the most abundant adipokine and exhibits anti-inflammatory, antiatherogenic and antidiabetic properties. Unlike other adipokines, it inversely correlates with body weight and obesity-linked cardiovascular complications. Diastolic dysfunction is the main mechanism responsible for approximately half of all heart failure cases, the so-called heart failure with preserved ejection fraction (HFpEF), but therapeutic strategies specifically directed towards these patients are still lacking. In the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 97 publications
1
16
0
6
Order By: Relevance
“…Animal studies have shown that adiponectin can inhibit cardiac hypertrophy and fibrosis, and reduce infarct size (174). Together these findings support the supposition that adiponectin might have therapeutic potential in HFpEF patients (176). However, circulating adiponectin levels are increased in both HFrEF and HFpEF (177).…”
Section: Unresolved Issuessupporting
confidence: 84%
See 2 more Smart Citations
“…Animal studies have shown that adiponectin can inhibit cardiac hypertrophy and fibrosis, and reduce infarct size (174). Together these findings support the supposition that adiponectin might have therapeutic potential in HFpEF patients (176). However, circulating adiponectin levels are increased in both HFrEF and HFpEF (177).…”
Section: Unresolved Issuessupporting
confidence: 84%
“…Adiponectin is the major adipokine produced by adipose tissue with anti-inflammatory, antidiabetic, anti-apoptotic, and anti-atherogenic properties (174, 176). Circulating adiponectin levels are decreased in obesity and type 2 diabetes and downregulation of adiponectin and its receptors is associated with insulin resistance and diabetes, as well as increased risk of HTN and coronary artery disease (174, 176). Animal studies have shown that adiponectin can inhibit cardiac hypertrophy and fibrosis, and reduce infarct size (174).…”
Section: Unresolved Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentro de las variables bioquímicas evaluadas era esperado encontrar a la glucosa como biomarcador de obesidad debido a que esta enfermedad también se encuentra relacionada con el desarrollo de diabetes tipo 2 (29) . La adiponectina, que constituye el 0,01 % al 0,05 % de todas las proteínas circulantes en plasma (7,8) , existe como monómero, trímero de bajo peso molecular (LMW), hexámero de mediano peso molecular (MMW) y como multímero de alto peso molecular (HMW) que comprende al menos 18 monómeros (26,30,31) . Sin embargo, parece que la combinación de HMW y MMW es la más relevante en la respuesta inflamatoria ya que esta combinación incrementa la liberación de interleucina-6, interleucina-8 y la metaloproteinasa MMP-3 (32) .…”
Section: Discussionunclassified
“…De hecho, algunas investigaciones tienen como objetivo el estudio de la administración exógena de adiponectina y su efecto en el mejoramiento de la condición del paciente (9,21,22) , no solo en enfermedades metabólicas, sino también en distrofia muscular de Duchenne (23) o mal de Alzheimer (24) . Revisiones y metaanálisis recientes encuentran algunas discrepancias entre estudios con respecto al uso de adiponectina como un biomarcador de enfermedades metabólicas por lo que todavía se recomienda incrementar el número de investigaciones de modo que este aspecto pueda ser aclarado (7,13,19,25,26) .…”
Section: Introductionunclassified